Developing Training Curriculum for Management Trainees Program at Company MTJ - Dwiki Fatur Rizki; Yohana Prisila Dian Pertiwi (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
Improving the competence and quality of management cadres is the main focus for many companies in various sectors. In an effort to prepare potential employees to take on future leadership roles, the development of a training curriculum is crucial. The purpose of this study is to explain the importance of designing an effective training curriculum for trainee management programs in MTJ companies. The study also aims and to explore the phenomena and challenges associated with the development of training curricula, focusing on the specific needs of companies and industries as well as the availability of adequate resources. This research uses qualitative methods with a case study approach Various studies have shown that a structured and relevant training curriculum can make a significant contribution in preparing employees to face the demands of the complex business world. However, in designing training curricula for trainee management programs, companies often face various obstacles, including adjustment to company needs, limited resources, and selection of appropriate learning methods. By understanding these challenges, strategic steps can be taken to address existing issues and design effective training curricula for trainee management programs. This research is expected to make an important contribution in the development of training curricula for trainee management programs in companies. With a better understanding of the challenges companies face in designing effective training curricula, strategic steps can be taken to overcome those obstacles. The results of this study can also provide insight to other companies in designing relevant and effective training programs. In addition, this research can be the basis for the development of advanced research in the field of human resource development and training management.